The “Academic Vernadskiy” station in the network of the Ukrainian magnetic observatories of INTERMAGNET - G. V. Melnyk; V. G. Bakhmutov (Ukrainian Antarctic Journal, 2008)
Information about the equipment and software support of the Ukrainian magnetic observatories of INTERMAGNET is presented. It is shown, that the observatory «Academic Vernadskiy» has the most modern equipment and the high-quality presentation of the final information.